Lower urinary tract symptoms in women with type 2 diabetes mellitus - (:unkn) unknown (Lippincott Williams and Wilkins, 2016)
PURPOSE: The aim of the study was to compare lower urinary tract symptoms (LUTS) in women with and without type 2 diabetes mellitus (DM). SUBJECTS AND SETTING: The sample was drawn from community-dwelling women in the province of Istanbul who were cared for in the diabetes outpatient clinic of Istanbul Medical School between January and June 2012. Two hundred forty-nine women with DM were compared to 255 women without DM cared for in the obstetrics and gynecology department of the same university hospital. The mean ages of the groups were 55.1 and 53.7 years, respectively. METHODS: Participants completed a questionnaire that queried sociodemographic and clinical characteristics; the Bristol Female Lower Urinary Tract Symptoms-Short Form (BFLUTS-SF) was used to evaluate LUTS. The questionnaire required 10 to 15 minutes to complete; participants completed the questionnaire in a private room of each of the respective outpatient clinics. RESULTS: No statistically significant differences were found when groups (women with and without DM) were compared based on age and cigarette smoking (P >.05). In contrast, BMI scores were significantly higher in the women with DM (P <.001). The cumulative BFLUTS scores and the filling and incontinence symptoms subscale sores (P <.001) were significantly higher in women with DM. No differences were observed in voiding symptoms (P =.347), sexual function (P =.380), and health-related quality of life (P =.142) subscale scores. The prevalence of storage symptoms nocturia, voiding frequency, urge incontinence, stress incontinence, frequency of incontinent episodes were higher among women with DM. In addition, women with DM were more likely to report the need to change clothing because of urinary leakage, effect of incontinence on daily tasks, and overall interference with daily activities of living. CONCLUSIONS: Women with type 2 DM are more likely to experience LUTS as compared to women without DM. Women with type 2 DM should routinely be assessed for LUTS. © 2016 by the Wound, Ostomy and Continence Nurses Society.
Keywords: Diabetes mellitus; Lower urinary tract symptoms; Urinary incontinence; Women